If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -9a = -2 Solving 2 + -9a = -2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -9a = -2 + -2 Combine like terms: 2 + -2 = 0 0 + -9a = -2 + -2 -9a = -2 + -2 Combine like terms: -2 + -2 = -4 -9a = -4 Divide each side by '-9'. a = 0.4444444444 Simplifying a = 0.4444444444
| 5x+125= | | 6/36=x/25 | | 15x=15-18 | | 9-X+6x=34 | | 23=-4 | | 16x-4=7x | | 12w+(-12)=0 | | 3(8n-2)=138 | | 4x-8x+13=5 | | 4v-9=9v | | 0=800+50x+3x^2 | | x/27=8/36 | | y=2x^2-8x-14 | | 6(p-6)=-84 | | 8(3g+2)-3g=3(5g-4)2 | | -5u-u=12 | | 5+r=17 | | 9x-9=x+15 | | 4.3x=11 | | 2y+4.5=11.5 | | 7x-5=2x+19 | | 24+7=38 | | 11x+8x= | | 3(8+7x)=192 | | 9x^3-6x^2-6x+4= | | 12+3p=8p+2 | | 3-8(2x-1)=27 | | 7+13=1 | | (a-bi)(a+i)=0 | | 7x+5-2x+8= | | -9=u-6 | | 4a+6a+8b-5b= |